Effectiveness of Synchronous-Asynchronous Method in E-Learning for Improved Learning Evaluation at Battuta University - Husein, Teuku Muhammad Ravyza; Siregar, M. Furqon; Syahputra, Dinur (Journal of Technology and Computer, 2024)
Modern learning, unlike traditional methods, is significantly influenced by technology. The rapid advancement of information technology, especially in the age of globalization, has transformed the educational landscape. The industrial revolution and globalization have necessitated the adoption of distance learning, which can be implemented effectively through technology without compromising quality. Technology has become integral to human life, revolutionizing how we work, socialize, and learn. The educational sector has embraced technological advancements to create innovative and engaging learning experiences. E-Learning, a prime example, leverages electronic media and the Internet to provide flexible and accessible learning opportunities. Using smartphones, laptops, or PCs allows students to learn from anywhere at any time, saving time and costs. E-Learning empowers students to maximize their learning potential regardless of circumstances.